2008
DOI: 10.1039/b718544h
|View full text |Cite
|
Sign up to set email alerts
|

A design concept of long-wavelength fluorescent analogs of rhodamine dyes: replacement of oxygen with silicon atom

Abstract: Replacement of the oxygen with a silicon atom on the rhodamine framework produces a strong red-emission fluorophore which has a high molar extinction coefficient and 90 nm red shift relative to rhodamine dye PY.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
168
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(173 citation statements)
references
References 51 publications
3
168
0
2
Order By: Relevance
“…2). 11 TMDHS exhibited a large bathochromic shift up to 90 nm in the absorption and emission wavelengths as a result of only a single atom change. The electrochemical and calculated data of these dyes indicate that the replacement of the O atom with a Si atom affected both the HOMO and LUMO energy levels (Fig.…”
Section: Design Concept Of Far-red To Near-infrared Xanthene Dyesmentioning
confidence: 99%
“…2). 11 TMDHS exhibited a large bathochromic shift up to 90 nm in the absorption and emission wavelengths as a result of only a single atom change. The electrochemical and calculated data of these dyes indicate that the replacement of the O atom with a Si atom affected both the HOMO and LUMO energy levels (Fig.…”
Section: Design Concept Of Far-red To Near-infrared Xanthene Dyesmentioning
confidence: 99%
“…Red fluorescent labels are particularly useful in life sciences, especially in biological fluorescence microscopy and single molecule spectroscopy (Fu et al 2008;Bruyneel et al 2010), because they require excitation photons of lower energy thus entailing less background due to autofluorescence. In addition, they are particularly attractive for stimulated emission depletion (STED) microscopy (Hell and Wichmann 1994;Klar et al 2000;Dyba et al 2003) because their fluorescence can be stopped with near-infrared wavelengths (typically > 750 nm) that are not only relatively benign to the sample, but also leave the visible spectrum open for the detection of other fluorophores.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Xiao, Nagano, and their respective co-workers (24,25) found that replacement of the oxygen atom in the xanthene moiety of tetramethylrhodamine with a silicon atom (Si-rhodamine) induces a dramatic red shift in emission of nearly 100 nm into the NIR region. Importantly, the fluorescence quantum yields of these probes could be modulated by over 100-fold through photoinduced electron transfer (PeT), rendering Sirhodamine a promising scaffold for sensor development (26)(27)(28).…”
mentioning
confidence: 99%